Online Microextraction Coupled with HPLC-ABTS for Rapid Analysis of Antioxidants from the Root of Polygonum bistorta. (17th January 2023) - Yang, Wei-Qi; Qian, Zheng-Ming; Wu, Meng-Qi; Gao, Jian-Li; Huang, Qi; Zou, Yuan-Sheng; Tang, Dan
Abstract : The root of Polygonum bistorta (PB) is a traditional Chinese medicinal plant material widely used in China. It has been commonly used for the treatment of hemostasis, detumescence, diarrhea, snake bite, and acute gastroenteritis. However, the research on the antioxidant properties and bioactive compounds from PB is inadequate. In the current research, an online microextraction (OLME) coupled with a high-performance liquid chromatography coupled with the 2, 2-nitrogen-di (3-ethyl-benzothiazole-6-sulfonic acid) diammonium salt antioxidant assay (HPLC-ABTS) system for rapid analysis of antioxidants from PB was proposed. The PB sample (0.17 mg) was online extracted by mobile phase (acetonitrile and 0.2% acetic acid); a Poroshell 120 SB-Aq column was used for separation; then, an online ABTS assay system was used for screening the antioxidants. Finally, ten components were found in PB, and among them, eight components possessed antioxidant activities. Furthermore, five components (gallic acid, neochlorogenic acid, caffeic acid, chlorogenic acid, and an unknown compound) were proved as major antioxidants when compared with rutin as an antioxidant marker. The results showed that the developed OLME-HPLC-ABTS system was a simple, rapid, green, and efficient instrument for the screening of antioxidants from PB, which provides a powerful tool for the discovery of natural antioxidants in Chinese medicines.